Creatine Kinase Is a Marker of Metabolic Syndrome in Qatari Women With and Without Polycystic Ovarian Syndrome - Noora Al-Hail (18140287) (2019)
Objective: To correlate features of metabolic syndrome with creatine kinase (CK) in women with and without polycystic ovary syndrome (PCOS). Design: Comparative cross-sectional analysis. Methods: Demographic and metabolic data from Qatari women aged 18–40 years from the Qatar Biobank (97 diagnosed with PCOS, 563 controls). The primary outcome was the association between plasma CK and features of metabolic syndrome. Results: CK increased when the waist circumference was >80 cm (p < 0.015) and when associated with 2 or more features of the metabolic syndrome (p < 0.01). CK correlated with BMI (p < 0.003) but not with waist/hip ratio. Overall, CK did not differ between PCOS and controls, rising equally in both as body mass index (BMI) increased. C reactive protein (CRP) was higher in obese PCOS (P < 0.05) compared to controls, but did not correlate with CK (p > 0.05). Conclusion: CK was associated with an increase in BMI, waist circumference >80 cm and 2 or more features of the metabolic syndrome, in accord with the central role of type II skeletal muscle fibers in energy metabolism and obesity. CK was, however, independent of the PCOS phenotype. Other Information Published in: Frontiers in Endocrinology License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3389/fendo.2019.00659